Distortions and tensile properties of 15-5PH steel cylinders with EBW and heat treatment. (3rd July 2019) - Fu, Pengfei; Mao, Zhiyong; Tang, Zhenyun
ABSTRACT: 15-5PH steel is one of the martensitic precipitation-hardened stainless steels, which is extensively applied in the aero shafts, and electron beam welding is a significant procedure to manufacture the parts. To verify the dimension accuracies and properties, EBW with oscillation was employed on the cylinders of 15-5PH steel. The welding distortions were measured, and the microstructures and tensile properties of the joints were investigated. The weld appearances of the cylinders were smooth, and the morphology was parallel. After EBW, the shrinkages of the cylinders were above −0.22 mm, and the welding distortions were −0.66 to −1.1‰, and the straightnesses were less than 1‰ due to the distortions. The martensites and a few austenites were in the welds of the cylinders after heat treatment, and the microhardnesses in the welds were 445 HV0.2, which were bigger and more homogeneous than those of the as-welded. The tensile strength and yield strength of the joints were respectively 1300 and 1150 MPa, which were higher than those of the as-welded joints, and the elongation rate of the joints was 10%. The microstructures and properties of the cylinders conformed to the aero shafts, which was attributed to the microstructure transformation with oscillation EBW and heat treatment.